Propuesta de agenda cultural para la recuperación del juego tradicional "Torneo de cintas a caballo" en la Parroquia de Peñaherrera, Imbabura - Balladares, Zamantha G. (2019)
The current document has the objective of recovering and strengthen the Peña Herrera's Community intangible heritage. It can be done by generating supplies in order to revitalize the traditional game "Torneo de Cintas a Caballo". This investigation is based on the mixed methods of poll and interview. This thesis consists of three chapters. The first one is about the inmaterial heritage and traditional games theoretical framework. The second one describes the research methodological design. The third one explains the analysis and interpretation of the results, proposing a cultural schedule in order to recover the ―Torneo de Cintas a Caballo‖. The results show a fading tradition through the last years but the Peña Herrera's sociocultural characteristics help to generate a recovering strategy.